On the problem of overcoming lexical interference in foreign language lessons - Assanova, D.; Knol, M. (KU Publ., 2022)
The article is dedicated to interpreting the irregularity of the difficulty of lexical interference in the foreign language speech of schoolchildren, as well as an attempt to propose a set of characteristic exercises aimed at overcoming this phenomenon. It is obligatory to make ready alumnus pl alumni with well-developed communication skills that appropriate them to achieve common apprehension and exchange existing ethnical acquaintance when contacting representatives of foreign language culture, as well as consideration for improving the overall level of culture and education of the graduate’s personality. The article presents the characteristics of this mechanism: the classifications and classification of interference are given, the psychological causes of this phenomenon in the mentality of learners are considered. The article concludes that in order to overtake lexical interference; it is paramount that the training substance incorporates carefulness of the most characteristic cases of lexical interference, as well as a leading rational procedure — planning, prognostication, and identification.
Шет тілі сабақтарында лексикалық кедергілерді жеңу мәселесіне
К проблеме преодоления лексической интерференции на уроках иностранного языка
Keywords: speech; vocabulary; lexical interference; language system; foreign language; language contact; synonym; antonym